Simulating Hamiltonian dynamics - Leimkuhler, B.; Reich, Sebastian (Cambridge, UK ; New York : Cambridge University Press, 2005)
Geometric integrators are timestepping methods, designed to exactly satisfy properties inherent in a system of differential equations. Beginning from basic principles of geometric integration and a discussion of the advantageous properties of such schemes, the book introduces a variety of methods and applications. Includes examples and excercises.
1. Introduction -- 2. Numerical methods -- 3. Hamiltonian mechanics -- 4. Geometric integrators -- 5. The modified equations -- 6. Higher-order methods -- 7. Constrained mechanical systems -- 8. Rigid body dynamics -- 9. Adaptive geometric integrators -- 10. Highly oscillatory problems -- 11. Molecular dynamics -- 12. Hamiltonian PDEs.
Includes bibliographical references (pages 357-373) and index.
Print version record.
Keywords: Hamiltonian systems; Hamiltonian sistemler; MATHEMATICS -- Differential Equations -- General; Hamiltonian systems; Hamiltonsches System; Konservatives System; Numerische Integration; Numerisches Verfahren; Simulation; Electronic books